OP51 Social inequalities in musculoskeletal ageing among community dwelling older men and women in the United Kingdom. (2nd September 2014) - Syddall, HE; Evandrou, M; Cooper, C; Aihie Sayer, A
Abstract : Background: The population of the United Kingdom (UK) is ageing; the already substantial burden of musculoskeletal disorders on health and social care systems will increase over time as the population ages. Social inequalities in health are well documented for the UK in general but little is known about social inequalities in musculoskeletal ageing. Methods: Using data from the 3225 'young-old' (59–73 years) community dwelling men and women who participated in the Hertfordshire Cohort Study, we explored social inequalities in musculoskeletal ageing: specifically, loss of muscle strength and physical function (PF); falls; Fried frailty; and osteoporosis. Socio-economic position was characterised by age left full-time education, parental social class at birth and own social class in adulthood, and current material deprivation by housing tenure and car availability. Results: 6.4% of men and 17.7% of women had no car and 19.3% of men and 23.1% of women did not own their home. Not owning one's home was associated with lower grip strength and increased frailty prevalence among men and women and with poorer self-reported short-form 36 (SF-36) PF among men. Reduced car availability was associated with lower grip strength and poorer SF-36 PF among men and women and with increased falls and frailty prevalence among men. Average grip ranged from 40.1 kg (95% CI 38.2–42.1) among men who did not own their home and had no cars, to 46.0 kg (95% CI 44.5–47.4) among home owners with three or more cars (for women 23.8 kg [95% CI 22.7–24.8] to 27.3 kg [95% CI 25.8–28.8]). In contrast, there was no evidence for social inequalities in fracture, dual X-ray absorptiometry (DXA) total femoral bone mineral density and bone loss rate, or peripheral quantitative computed tomography (pQCT) strength strain indices for the radius or tibia. Further analysis and review of the literature suggested that social variations in height, fat mass, diet and physical activity are likely to have mediated these contrasting social gradients in muscle and bone. Conclusion: A subgroup of older men and women in the UK face increased levels of material deprivation in combination with greater loss of muscle strength and physical function. These people urgently need the government to commit to reform of the funding system for adult care and support. Our results suggest that clinical interventions to reduce the loss of muscle mass and function with age should be targeted proportionately across the social gradient; strategies to reduce fracture and osteoporosis should continue to have a universal population focus.